2022
DOI: 10.2215/cjn.14021021
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban versus Warfarin for Treatment of Venous Thromboembolism in Patients Receiving Long-Term Dialysis

Abstract: Background and objectivesThe association of apixaban compared with warfarin for the treatment of venous thromboembolism in patients receiving maintenance dialysis is not well studied.Design, setting, participants, & measurementsWe conducted a retrospective cohort study of Medicare fee-for-service beneficiaries receiving dialysis using United States Renal Data System data from 2013 to 2018. The study included patients who received a new prescription for apixaban or warfarin following a venous thromboembolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…A recently published analysis using USRDS data to compare apixaban and warfarin to treat acute VTE in patients with ESKD also found a lower adjusted hazard ratio of major bleeding but also noted a significantly lower adjusted hazard ratio of recurrent VTE than in our study. 29 Our analysis differed from that by Wetmore et al in terms of covariates, the relationship of VTE diagnosis and index prescription timing for inclusion to cohort, the technique for ensuring patients were on maintenance dialysis, controlling for year of index prescription, and definition of recurrent VTE.…”
Section: Discussionmentioning
confidence: 81%
“…A recently published analysis using USRDS data to compare apixaban and warfarin to treat acute VTE in patients with ESKD also found a lower adjusted hazard ratio of major bleeding but also noted a significantly lower adjusted hazard ratio of recurrent VTE than in our study. 29 Our analysis differed from that by Wetmore et al in terms of covariates, the relationship of VTE diagnosis and index prescription timing for inclusion to cohort, the technique for ensuring patients were on maintenance dialysis, controlling for year of index prescription, and definition of recurrent VTE.…”
Section: Discussionmentioning
confidence: 81%
“…94 Chen et al 95 described 68 HD patients treated with apixaban for VTE and reported the occurrence of major bleeding in 13.2% of patients and recurrent VTE in 7.4% of patients. 95 Finally, Wetmore et al 96 ○ Administration post-HD, compared to healthy controls: AUC 56% higher • Limited removal of rivaroxaban by HD: ○ Administration pre-HD, compared to post-HD: AUC 5% lower Abbreviations: AF, atrial fibrillation; AUC, area under the plasma concentration versus time curve; BID, twice daily; Cmax, maximum plasma concentration; CrCl, creatinine clearance; ESKD, end-stage kidney disease; HD, haemodialysis; OD, once daily.…”
Section: Apixabanmentioning
confidence: 97%
“…of 12 206 VTE patients on HD (74% treated with warfarin, 26% treated with apixaban) and reported that apixaban was associated with less recurrent VTE (HR 0.58, 95% CI 0.43-0.77) and less major bleeding events (HR 0.78, 95% CI 0.62-0.98) compared to warfarin. 96 The retrospective study by Knueppel et al 97 compared the use of standard (5 mg twice daily) versus reduced dose of apixaban (2.5 mg twice daily) in 203 patients with a broader definition of severe or end-stage renal disease (defined as CrCl <25 mL/ min, creatinine >2.5 mg/dL, CKD stage 4-5, or HD). The reduced dose was associated with lower clinically relevant bleeding events than the standard dose (3.8% vs. 14.4%, respectively, p = 0.02), without increasing the risk of recurrent VTE (7.7% vs. 6.4%, p = 0.78).…”
Section: T a B L E 4 (Continued)mentioning
confidence: 99%
“…One could argue that it could be used in patients with excellent control of their mineral metabolism but our data show that warfarin increases arterial calcification in patients with normal renal function and presumably normal mineral metabolism. With data now showing that direct‐acting oral anticoagulants can be safe and effective in ESRD, 19–21 including in patients with calcific uremic arteriolopathy, 22,23 there seems little need to use warfarin. Unfortunately, as in the patient presented above, these newer agents are not approved for anticoagulation in patients with mechanical heart valves.…”
Section: Figurementioning
confidence: 99%